Бесноватый цесаревич: [роман] / Александр Яманов - Яманов Александр (Попаданец, 2022)
Экземпляры: ЦБ (20241126) / Инвентарный номер: 61838 / Цена: 546.04 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Я 54 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44